Rheological properties and slurry behaviour in hard rock drilling - Kamyab, Mohammadreza; Rasouli, Vamegh; Mandal, S.; Cavanough, G. (Maney Publishing, 2013)
Coiled tubing (CT) drilling offers more efficient drilling operations compared to normal drilling practises resulting in lower operational costs and drilling time in oil and gas operations. This technology is recommended to be used for mineral exploration drilling in hard rock. This requires drilling micro-boreholes at very high speed with small size cuttings. A large volume of such small size cuttings can influence the rheological properties of the drilling fluids significantly. The aim of this study is to understand the effect of small size inert cuttings on the rheological properties of drilling fluids and its consequences on pressure drop changes in the annulus space. Experimental tests were performed on cuttings collected from a mining site, and the results indicated that the fluid rheology is sensitive to the cuttings size. This conclusion suggests that careful measurement of rheological properties of the mud is necessary when it is designed for drilling hard rocks.